PENEGAKAN HUKUM TERHADAP KASUS POLIGAMI SECARA NIKAH SIRI BERDASARKAN PUTUSAN HAKIM PADA PERKARA NOMOR 363/PID.B/2013/PN.Tng DAN PERKARA NOMOR 114/PID/2007/PT.Btn - Nurdianti Nurdianti; Zulfikar Jayakusuma; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Polygamy is a marriage where a partner of the sex who has more than one partner at the same time with the terms and conditions. In Article 279 of the Criminal Code it has been stated that prohibiting marriage more than once will be punishable by imprisonment of 5 (five) years if it does not meet the requirements. In decision number 363/Pid.B/2013/PN.Tng which recognizes the validity of Siri marriage and decision number 114/Pid/2007/PT.Btn which does not recognize the validity of Siri marriage against polygamists.This research uses library research method. This research was conducted by examining the laws, documents and literature relating to the research material. The research approach used in this research is descriptive analysis, which uses research on the systematic system of law and examines the norms that exist in criminal law and criminal law rules, especially the Criminal Code (KUHP) and Law 1 of 1974 concerning Marriage, then the data will be analyzed based on normative-juridical.From the results of research and discussion it can be concluded that, Firstly, law enforcement in the decision of the judge against the polygamist perpetrators with case number 363/Pid.B/2013/PN.Tng that the Panel of Judges has been right in examining and deciding the case. Whereas in the decision number 114/Pid/2007/PT.Btn that the Panel of Judges was negligent in examining and deciding the case. The judge's interpretation in the above ruling is to acknowledge the validity of the marriage and not acknowledge the validity of the marriage itself. Whereas the factors causing the uneven uniformity of the judge's decision are that the judge has freedom in deciding the case, the judge's self, and the thought contingency of the judge.Keywords: Polygamy, Siri Marriage, Judge's Decision